Prevalence and clinical characteristics of uveitic glaucoma: multicentric study in Bogotá, Colombia (2023)
OBJECTIVES: To describe the clinical features of patients diagnosed with uveitic glaucoma (UG) and ocular hypertension secondary to uveitis (OHT-SU). METHODS: A multicentric cross-sectional study using medical records of patients with uveitis between 2013 and 2021. Uveitis and glaucoma specialists examined all patients. Variables were analyzed using the chi-square or Fisher’s exact test for categorical variables. Additionally, t test, Mann–Whitney, and Kruskal–Wallis variance analysis were used for continuous variables. Finally, a Kaplan–Meier survival analysis for UG and OHT-SU development over time was done. RESULTS: Of the 660 clinical records reviewed of patients with uveitis, 191 (28.9%) had OHT-SU in at least one visit, and 108 (16.4%) of them developed UG. In all ages, females were more affected than males. Anterior uveitis was the main anatomic localisation, and non-granulomatous, recurrent, and inactive uveitis were the most frequent clinical features. The mean fnal visual acuity was 0.3 (0.0–1.0) LogMAR. Also, 95.8% of the patients had additional sequelae related to uveitis regardless of UG and OHTSU. Interestingly, males had earlier affection, with statistical signifcance in OHT for adults (P = 0.036) and UG for children (P = 0.04). Of all patients, 81.1% received topical hypotensive treatment and 29.8% required a surgical procedure. CONCLUSIONS: UG and OHT-SU are common complications of uveitis in the Colombian population. These sight-threatening conditions were more common and appeared sooner in men at any age. Our results suggest that earlier and more aggressive treatment with topical hypotensive agents could positively infuence the visual outcomes and the requirement of surgical procedures.